2014
DOI: 10.5861/ijrset.2014.744
|View full text |Cite
|
Sign up to set email alerts
|

The pedagogical utility of audio-visual aids on extrovert and introvert Iranian intermediate EFL learners' speaking ability

Abstract: This study explored the relationship between the use of audio-visual aids to improve the speaking ability of Iranian intermediate EFL learners and their personality type; namely, introversion/extroversion. To this end, The Comprehensive English Language Test (CELT) was given to 250 students to homogenize the sample. Out of this, 120 students whose scores fell one standard deviation above and below the mean were regarded as intermediate. Having found the homogeneous participants, the Eysenck Personality Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The result showed that mean score of extrovert student was higher than mean score of introvert students (78.17<75.76). This result line with research by Khodareza and Taheri (2015), also found there was difference between extrovert and introvert student in speaking ability. Their research also shows that extroverts are generally better at than introverts.…”
Section: Discussionsupporting
confidence: 91%
“…The result showed that mean score of extrovert student was higher than mean score of introvert students (78.17<75.76). This result line with research by Khodareza and Taheri (2015), also found there was difference between extrovert and introvert student in speaking ability. Their research also shows that extroverts are generally better at than introverts.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, there are studies that deal with the impact of AVRs on particular language skills. Such studies ( 1) focus on the usefulness of AVRs in building students' competence in pronunciation (Gilakjani, 2011;Ranasinghe & Leisher, 2009), (2) elaborate on the effects of AVRs in promoting target language communication, that is, the speaking skills of students (Çakir, 2006;Natoli, 2011;Ramin, Reza, & Nazli, 2014), or (3) study the importance of video instruction in teaching vocabulary (Gross, 1993;Wright & Haleem, 1991). They, furthermore, take listening skills into consideration to investigate how visual material can be used as a teaching strategy for improving listening comprehension skills (Potosi, Loaiza, & Garcia, 2009), showing that video sessions contribute to a better mastery of listening skills and a greater motivation for students to participate in conversation.…”
Section: Recent Research On the Audio-visual Resources In Efl/esp Coursesmentioning
confidence: 99%